2013
DOI: 10.3109/10428194.2013.827187
|View full text |Cite
|
Sign up to set email alerts
|

Hairy cell leukemia treated initially with purine analogs: a retrospective study of 107 patients from the Spanish Cooperative Group on Chronic Lymphocytic Leukemia (GELLC)

Abstract: Purine analogs are highly effective in hairy cell leukemia (HCL) with response rates of 85%, but with many late relapses. We have retrospectively reviewed the clinical data from 107 patients treated with pentostatin (n = 27) or cladribine (n = 80), to investigate the long-term efficacy and to identify factors associated with the treatment-free interval (TFI). Complete remission and minimal residual disease (MRD) rates were similar in both groups. Median TFI was shorter (95 vs. 144 months) in the pentostatin gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
2
21
0
1
Order By: Relevance
“…These results have been confirmed by recent studies, all retrospective (Table 1), including long-term data from three earlier series: from the Scripps Clinic [37], from Bologna [18], and our own series, updated in 2009 [19], and reviewed in 2011 with a focus on the implications for clinical practice [15]. There are also two series, from Spain and France, with some minor overlap of patients from previous reports [38], [39] and three new reports from Turkey, India and Mexico [40], [41], [42]. Four of these studies report results with both cladribine and pentostatin, while the other four report only cladribine.…”
Section: Updated Results From the Published Seriessupporting
confidence: 80%
See 3 more Smart Citations
“…These results have been confirmed by recent studies, all retrospective (Table 1), including long-term data from three earlier series: from the Scripps Clinic [37], from Bologna [18], and our own series, updated in 2009 [19], and reviewed in 2011 with a focus on the implications for clinical practice [15]. There are also two series, from Spain and France, with some minor overlap of patients from previous reports [38], [39] and three new reports from Turkey, India and Mexico [40], [41], [42]. Four of these studies report results with both cladribine and pentostatin, while the other four report only cladribine.…”
Section: Updated Results From the Published Seriessupporting
confidence: 80%
“…This led to a CR in 14 patients (78%) [15]. Similarly, in the Spanish series 8 patients in PR were treated with a second cycle of cladribine, which led to a CR in 6 patients (75%) [38]. In the Indian series 2 patients received a second cycle of treatment at 6–8 months and both achieved a CR [41].…”
Section: Updated Results From the Published Seriesmentioning
confidence: 92%
See 2 more Smart Citations
“…MRD was initially quantified using immunohistochemistry markers, and was identified in 13–26% of patients following treatment with pentostatin or cladribine [9]. More sensitive tests including flow cytometry and PCR for immunoglobulin gene rearrangement using consensus or sequence specific primers demonstrate MRD in 27–50% of patients who are in CR [10, 11]. Application of digital PCR found that all patients treated with vemurafenib had detectable MRD by quantification of mutant BRAF in bone marrow despite being in CR [12].…”
mentioning
confidence: 99%